Oumu no Gami / Siti Ermi Syahira Abdul Jamil - Abdul Jamil, Siti Ermi Syahira (Faculty of Art and Design, 2021)
Life is an exquisite and bewildering journey as it is enriched with a variety of surprising elements. The concept is unpredictable, unknown, and full of mysterious elements. The Oumu no Gami is a metaphor of my life journey. The Oumu is representing me, myself, and I. Every single folding technique visualized the complex beauty of my life experiences; up and down, black and white, and the happy and sad moments which are full of memories and expression while the texture displayed the outline of my journey. Life can’t be paused, stopped nor rewind, and that is the secret of a colorful journey that has delicately constructed as my life- inspired artwork, Oumu no Gami.